THE ROLE OF ICT IN THE TEACHING AND LEARNING OF MATHEMATICS IN ELEMENTARY EDUCATION (Annual of the Faculty of Philosophy in Skopje, 2024)
Technology is an essential aspect of everyday life, thus the growth and integrationof information and communication technology (ICT) in learning and teaching isexpected. Beginning with the origins of technology based on mathematics as a science,we narrow our focus in this scholarly study on the use of ICT in the teaching andlearning of mathematics in elementary education. We focused on studying the impactof ICT on the teaching and learning process, as well as the usage of ICT tools in thedevelopment of knowledge in mathematics. The goal of this systematic analysis is toshow the benefits of integrating ICT into mathematics teaching and learning, as well asthe constraints and challenges that elementary school teachers and students encounter.Our comprehensive analysis of pertinent theoretical and empirical findings ledus to the general conclusion that teacher proficiency with the new technology plays amajor role in the integration of ICT. The positive impact of ICT on mathematics teachingand learning is undeniable, because technology reduces logistics in the planningand implementation of instruction, increases interaction in the classroom, and encouragesmathematics learning through the visualization of abstract concepts and processes,while also allowing for independent study.
Keywords: ICT; teaching process; learning process; mathematics; elementary education